Green Innovation Behavior Toward Sustainable Tourism Development: A Dual Mediation Model - Li, XiaoJuan (Frontiers in Psychology, 2022)
The rapid increase in globalization has fostered the emerging ecological challenges to halt human civilization, substantially highlighting the need for environmental management. The study's primary objective is to analyze the impact of environmental perception of corporate social responsibility (CSR) and attitude toward environmental CSR on sustainable tourism development while considering the mediating role of national park identification goals and employee pro-environmental behavior. The data was collected from the 338 employees working in the Chinese tourist firms'. The study variable’s reliability & validity was checked by using Composite Reliability (CR) and Average Variance Extracted (AVE). Study results show that environmental CSR perception and attitude toward environmental CSR positively impact sustainable tourism development, national park Goal identification, and employee pro-environmental behavior. National Park goal identification and employee pro-environmental behavior mediate between sustainable tourism development and environmental perception of corporate social responsibility and attitude toward environmental CSR.